Are Antibiotics The Hidden Culprit Behind Gut Microbiome Chaos in Children? A Comprehensive Systematic Review - Albert; Dicky (The Indonesian Journal of General Medicine, 2024)
Background: This review synthesizes diverse studies to understand antibiotic effects on microbiome composition and function, informing strategies to mitigate dysbiosis in pediatric populations.  Methods: The review adhered to PRISMA 2020 standards and analyzed full-text English literature from 2014 to 2024. Literature sources included PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of  500 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, ten articles directly relevant to the systematic review were selected for full-text reading and analysis. Discussion: Antibiotics, particularly azithromycin, show varied impacts on gut microbiota diversity and composition in children. Studies highlight specific taxa affected and potential long-term consequences, underscoring the need for cautious antibiotic use to preserve microbial health in pediatric populations. Conclusion: The review emphasizes the complex and context-specific effects of antibiotics on children's gut microbiota. It calls for judicious antibiotic prescribing to mitigate potential long-term disruptions to microbial diversity and function, crucial for maintaining overall health in pediatric populations.